Murdannia loriformis: a review of ethnomedicinal uses, phytochemistry, pharmacology, contemporary application, and toxicology - Che Sulaiman, Intan Soraya; Mohamad, Azham; Ahmed, Osumanu Haruna (Hindawi, 2021)
This review provides an updated and comprehensive overview on the ethnomedicinal use, phytochemistry, pharmacology, and toxicology of M. loriformis. Phytochemical analysis of M. loriformis revealed that it is composed of phenolics, flavonoids, condensed tannins, chlorophylls, alkaloids, and steroids. Numerous compounds including syringic acid, ß-O-D glucopyranosyl-2-(2′-hydroxy-Z-6′-enecosamide) sphingosine, isovitexin, and 3β-O-D-glucopyranosyl-24ξ-ethylcholest-5-ene have been identified and isolated from this plant species. The present review attempts to bridge the gap between traditional use and pharmacological studies of M. loriformis while improving their existing therapeutic agents and product applications based on this plant.